Effects of Low Molecular Weight Sulfated Galactan Fragments From Botryocladia Occidentalis on the Pharmacological and Enzymatic Activity of Spla2 From Crotalus Durissus Cascavella - Toyama, M. H. [UNESP]; Toyama, D. O.; Torres, V. M.; Pontes, G. C.; Farias, W. R. L.; Melo, F. R.; Oliveira, S. C. B. [UNESP]; Fagundes, F. H. R. [UNESP]; Diz Filho, E. B. S. [UNESP]; Cavada, B. S. (Springer, 2010)
Low molecular weight fragments of sulfated galactans (Boc-5 and Boc-10) from the red algae Botryocladia occidentalis significantly inhibited Crotalus durissus cascavella sPLA2 enzymatic activity. Equimolar ratios of sPLA2 to Boc-5 or Boc-10 resulted in allosteric inhibition of sPLA2. Under the conditions tested, we observed that both Boc-5 and Boc-10 strongly decreased edema, myonecrosis, and neurotoxicity induced by native sPLA2.
Keywords: Botryocladia occidentalis; Crotalus durissus cascavella; Secretory phospholipase A2 (sPLA2); Edema; Myonecrosis